Transcriptomics Applied to the Study of Chagas Disease Vectors - Borsatto, Kelly Cristine [UNESP]; Coronado, Monika Aparecida; Galvao, Cleber; Arni, Raghuvir Krishnaswamy [UNESP]; Alevi, Kaio Cesar Chaboli [UNESP] (Amer Soc Trop Med & Hygiene, 2022)
Chagas disease is a neglected disease caused by the protozoan Trypanosoma cruzi, and is transmitted mainly by the feces of contaminated triatomines. Knowledge of the biological, ecological, behavioral, genetic, taxonomic, and systematic aspects of these vectors can contribute to the planning of vector control programs, because all species are considered to be potential vectors of Chagas disease. Transcriptomic studies, in general, provided a new view of the physiology of triatomines (aiding in the knowledge of reproductive aspects of the hematophagy process and even the immune system and the sensory apparatus) and even contributed, as a new tool, to the taxonomy and systematics of these insects. Thus, we conducted a review of the transcriptomic studies on Chagas disease vectors.